Basement v3: A modular freeware for river process modelling over multiple computational backends. (September 2021) - Vanzo, Davide; Peter, Samuel; Vonwiller, Lukas; Bürgler, Matthias; Weberndorfer, Manuel; Siviglia, Annunziato; Conde, Daniel; Vetsch, David F.
Abstract: Modelling river physical processes is of critical importance for flood protection, river management and restoration of riverine environments. Developments in algorithms and computational power have led to a wider spread of river simulation tools. However, the use of two-dimensional models can still be hindered by complexity in the setup and the high computational costs. Here we present the freeware basement version 3, a flexible tool for two-dimensional river simulations that bundles solvers for hydrodynamic, morphodynamic and scalar advection-diffusion processes. basement leverages different computational platforms (multi-core CPUs and graphics processing units GPUs) to enable the simulation of large domains and long-term river processes. The adoption of a fully costless workflow and a light GUI facilitate its broad utilization. We test its robustness and efficiency in a selection of benchmarks. Results confirm that basement could be an efficient and versatile tool for research, engineering practice and education in river modelling. Highlights: Basement v3 simulates different 2D river physical processes. A suite of test cases proves the tool's robustness and validity. Modularization and parallelization enable efficient large domain applications. Multiple computational backends readily available. Graphical User Interface available for simulation setup.